EKOSISTEM TERUMBU KARANG DAN KONDISI OSEANOGRAFI PERAIRAN KAWASAN WISATA BAHARI LOMBOK - Muhlis (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
The research that was carried out in Lombok marine tourism is purposed to find out 1) the condition of coral reef ecosystem 2) the condition of waters oceanography and 3) the relationship between the conditions of coral reef ecosystem and the oceanography condition of Lombok marine tourism. The observation was conducted with the line transect method in the windward zone and leeward zone, in 3 meters and 10 meters depth with three test times. The condition of coral reef that would be analyzed is about 1) percentage of the coral cover 2) the death index of coral 3) the form of growth coral, whereas the oceanography condition that would be analyzed is the temperature, salinity, the pH, DO, the brightness, and the flow speed. Knowing the relationship between the condition of coral reefs and the condition of oceanography will be carried out with the analysis of regression. The result shows that the condition of coral reefs ecosystem in windward zone has 36.9% cover coral, the death index of coral 0.17, the form growth coral that was found is 13 kinds 251 number of forms of the growth coral, while the condition of coral reef ecosystem in leeward zone reached 23.72% cover coral, the death index of coral 0.45, the form of growth coral that was found is 11 kinds 276 number of forms of the growth coral. The condition of oceanography factor of windward zone has 22,36 meters brightness, the temperature 27.52◦C, the flow speed 4.77 m./sec, the salinity 33.21 Ppt, the pH 7.56 and the protracted oxygen 6.41 Mg.l-1, the brightness of leeward zone reached 14.36 meter, the temperature 27.83◦C, the speed of the flow 2.68 m./sec, the salinity 31.54 Ppt, the pH 7.77 and the protracted oxygen 5.40 Mg.l-1. There is relationship between the oceanographic factor and the condition of coral reef ecosystem, from the sixth oceanographic factors, salinity has the highest effective contribution that is 49.79%, and the lowest is the pH that only 1.52%.